(untitled) (Texas Journal of Philology, Culture and History, 2024)
This article explores the use of proper names in phraseology, focusing on idioms, proverbs, and sayings that contain proper names. Such expressions originate from a variety of sources, including literature, mythology, fables, and everyday language. The study bridges two linguistic branches: phraseology and onomastics. Through the componential, cognitive, contextual, and semantic analysis of various idioms across cultures and languages, the paper illustrates how personal names evolve into idiomatic expressions, acquiring symbolic meanings